2015
DOI: 10.1590/1809-4430-eng.agric.v35n3p430-441/2015
|View full text |Cite
|
Sign up to set email alerts
|

Deficit irrigation in grapevine cv. Syrah during two growing seasons in the brazilian semiarid

Abstract: Irrigation plays an important role for grape's yield as well as on its quality for winemaking. Thus, the effects of deficit irrigation strategies on yield and quality of wine grapes cv. Syrah were evaluated in Petrolina, State of Pernambuco, Brazil. Evaluations were carried out throughout the second and third growing seasons, which were from November 2010 to February 2011 (rainy season) and from May to September 2011 (dry season), respectively. Vines were drip irrigated and the experimental design was complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
9
0
4
Order By: Relevance
“…Correlation analysis also indicated that canopy reflectance measurements had a positive associations with BM and V100 for the 2018 growing season only (Table 2). Water deficit can reduce the size of berries and modify their composition (Bassoi et al, 2015). Therefore, the higher levels of water deficit observed in the low NDVI zone of area 1 at 120 dap in 2018 (Figure 5C) may explain that correspondence.…”
Section: Grape Berry Attributesmentioning
confidence: 91%
“…Correlation analysis also indicated that canopy reflectance measurements had a positive associations with BM and V100 for the 2018 growing season only (Table 2). Water deficit can reduce the size of berries and modify their composition (Bassoi et al, 2015). Therefore, the higher levels of water deficit observed in the low NDVI zone of area 1 at 120 dap in 2018 (Figure 5C) may explain that correspondence.…”
Section: Grape Berry Attributesmentioning
confidence: 91%
“…Na agricultura irrigada o uso de metodologias para quantificar a aplicação de água é um fator importante para preservação dos recursos hídricos e consequentemente evitar problemas na produção agrícola pela falta (BASSOI et al, 2015;SHELLIE;BROWN, 2012;YONTS et al, 2018) ou pelo excesso de água (DA SILVA et al, 2019).…”
Section: Evapotranspiração E O Uso De Cobertura Vegetal Na Agricultunclassified
“…Na agricultura irrigada o uso de metodologias para quantificar a aplicação de água é um fator importante para preservação dos recursos hídricos e consequentemente evitar problemas na produção agrícola pela falta (BASSOI et al, 2015;SHELLIE;BROWN, 2012;YONTS et al, 2018) Devido a redução da evaporação, alguns autores (BONACHELA et al, 2001;DING et al, 2013;PAÇO et al, 2019;SALADO-NAVARRO;SINCLAIR;MORANDINI, 2013;YONTS et al, 2018) realizaram diversos estudos sobre a cobertura vegetal (ALLEN; PEREIRA, 2009) em função da ETc e altura da planta, estes autores obtiveram a seguinte equação (3):…”
Section: Evapotranspiração E O Uso De Cobertura Vegetal Na Agricultura Irrigadaunclassified